Assessing the Reliability of the Framework for Equitable and Effective Teaching With the Many-Facet Rasch Model - Govindasamy, Priyalatha; del Carmen Salazar, Maria; Lerner, Jessica; Green, Kathy E. (Frontiers in Psychology, 2019)
This paper reports results of an empirical assessment of a newly developed measure designed to assess apprentice teaching proficiency. In this study, Many Facets Rasch model software was used to evaluate the psychometric quality of the Framework for Equitable and Excellent Teaching (FEET), a rater-mediated assessment. The analysis focused on examining variability in (1) supervisor severity in ratings, (2) level of item difficulty, (3) time of assessment, and (4) teacher apprentice proficiency. Added validity evidence showed moderate correlation with self-reports of apprentice teaching. The findings showed support for the FEET as yielding reliable ratings with a need for added rater training.